Trauma surgery by general surgeons: Still an option for proximal femoral fractures?. Issue 2 (February 2017) - ,; van den Brand, J.G.H. (Han); van Velde, Romuald; Haverlag, Robert; Ultee, Jan M.; Postma, Victor A.; Twigt, Bas A.; van Dijkman, Bart A.; Heres, Pieter; Winkelhagen, Jasper; Klooster, Mariska; Toor, E.J. (Annelies); et al.
Abstract: Introduction: Surgery for proximal femoral fractures in the Netherlands is performed by trauma surgeons, general surgeons and orthopaedic surgeons. The aim of this study was to assess whether there is a difference in outcome for patients with proximal femoral fractures operated by trauma surgeons versus general surgeons. Secondly, the relation between hospital and surgeon volume and postoperative complications was explored. Methods: Patients of 18 years and older were included if operated for a proximal femoral fracture by a trauma surgeon or a general surgeon in two academic, eight teaching and two non-teaching hospitals in the Netherlands from January 2010 until December 2013. The combined endpoint was defined as reoperation or surgical site infection. Multivariate analysis was used to adjust for patient and fracture characteristics and hospital and surgeon volume. Categories for hospital volume were >170/year (high volume), 96–170/year (medium volume) and <96/year (low volume). Results: In 4552 included patients 2382 (52.3%) had surgery by a trauma surgeon. Postoperative complications occurred in 276 (11.6%) patients operated by a trauma surgeon and in 258 (11.9%) operated by a general surgeon (p = 0.751). When considering confounders in a multivariate analysis, surgery by trauma surgeons was associated with less postoperative complications (OR 0.746; 95%CI 0.580–0.958; p = 0.022). Surgery in high volume hospitals was also associated with less complications (OR 0.997; 95%CI 0.995–0.999; p = 0.012). Surgeon volume was not associated with complications (OR 1.008; 95%CI 0.997–1.018; p = 0.175). Conclusion: Surgery by trauma surgeons and high hospital volume are associated with less reoperations and surgical site infections for patients with proximal femoral fractures.